Improving Practicum Assessment Instruments for IT Programme by Using Action Research Approach (S/O 14142) - Muhd Darus, Norida; Che Pa, Noraziah (UUM, 2019)
Good Practicum instruments are crucial in ensuring the accuracy of the assessment and how well students to be prepared to face the industry as stated in IR 4.0. Due to the drawbacks of the existing assessment tools, an improved design of assessment instruments are needed. A better version of the tools are crucial in indicating the real situation and indicator of Practicum performance. In this article, we proposed an improved design of the Practicum assessment instruments responsive to unsatisfactory feedbacks from industry regarding Practicum performance and assessment. A combination of Design Science Research methodology and Action Research are employed in designing the improved instruments. The improved design is focusing on student learning needs and policy by integrating Practicum elements, university’s expectation and industry’s expectation. Emphasises are given on integrating important elements in achieving Practicum learning outcomes. The improved design is hope to be capable in measuring Practicum performance accurately and can be used to further assess many other aspects that reflect Practicum performance in preparing IT experts to face the industry as stated in IR4.0.